A two-way nesting framework for ocean models. (July 2019) - Herzfeld, M.; Rizwi, F.
Abstract: Two-way nesting is becoming a popular method to resolve limited area domains at high resolution. However, implementation of two-way nesting into ocean models is not a trivial process. We present an alternative two-way nesting framework that leverages off existing functionality present in many ocean codes, including arrays to store data exchanged between grids, data exchange protocols and re-gridding. An important element of this is the use of existing open boundary infrastructure to store and apply the data exchanged in two-way nesting, reduce specification error at the boundary and circumvent coupling at the barotropic levels. The resulting two-way system consists of models that operate in isolation of each other and can be considered autonomous in the sense that no overarching coupling infrastructure is required to orchestrate the two-way nesting, and models for respective grids can operate independently with communication achieved only via the sending and receiving of packets of self-describing information. Highlights: We present a 2-way nesting framework using largely existing functionality in an ocean code. Open boundary conditions are used to increase stability and avoid coupling at the barortopic level. We test the framework in a baroclinic vortex test case. We also test the framework in a real world application in the Great Barrier Reef.